A NEW RECORD OF CHLOOTHAMNUS BUSE (POACEAE: BAMBUSOIDEAE) FROM SUMBAWA ISLAND AND NOTES ON THE GENUS IN MALESIA - I Putu Gede P. Damayanto; Ida Bagus Ketut Arinasa; I Gede Tirta; Elizabeth A. Widjaja (Floribunda, 2020)
I Putu Gede P. Damayanto, Ida Bagus K. Arinasa, I Gede Tirta, Elizabeth A. Widjaja. 2020. Rekaman Baru Chloothamnus Buse (Poaceae: Bambusoideae) dari Pulau Sumbawa dan Catatan Tentang Marganya di Malesia. Floribunda 6(4): 127–132. — Dari hasil eksplorasi yang dilakukan di P. Sumbawa ditemukan jenis Chloothamnus schmutzii yang semula dilaporkan hanya tumbuh di daerah Manggarai, P. Flores. Dengan ditemukannya jenis ini membuktikan bahwa Sumbawa mempunyai hubungan erat secara geografi dengan daratan Flores Barat. Pertelaan jenis C. schmutzii disiapkan untuk melengkapi pertelaan jenisnya yang waktu dipertelakan tidak lengkap. Foto pelepah buluh spesimen C. schmutzii disajikan. Secara keseluruhan, terdapat 11 jenis Chloothamnus di Malesia (delapan di Papua New Guinea, dua di Kepulauan Sunda Kecil, satu di Jawa). I Putu Gede P. Damayanto, Ida Bagus K. Arinasa, I Gede Tirta, Elizabeth A. Widjaja. 2020. A New Record of  Chloothamnus Buse (Poaceae: Bambusoideae) from Sumbawa Island and Notes on the Genus in Malesia. Floribunda 6(4): 127–132. — From the exploration occurred at Sumbawa Island, it was found that Chloothamnus schmutzii which was reported only found in Manggarai District, Flores Island. Through the discovery of this species proves that Sumbawa has close relationship geography with the West Flores mainland. The description of C. schmutzii is presented to fulfil the species description which was not completed when it is described. The photograph of culm-sheath of C. schmutzii specimen is presented. Overall, there are 11 species of Chloothamnus in Malesia (eight in Papua New Guinea, two in the Lesser Sunda Islands, one in Java).